Laporan Indonesia Social Investment Forum 2025: Melampaui Batasan Sosial, Membangun Masa Depan Berkelanjutan dengan Inovasi dan Kolaborasi - Agusta, Ivanovich; Ivanovich; Hidriansjah, Iqri Sulizar (CANTING: Indonesian Community Development and Social Investment Journal, 2026)
Indonesia faces stagnant SDG progress, requiring acceleration through social innovation. This report summarizes transformative strategies from ISIF 2025, emphasizing the integration of ESG frameworks and double materiality to mitigate corporate climate risks. It addresses integrated mine closure (closure-by-design) and community-based conservation utilizing ToC, LFA, and SROI instruments to ensure impact accountability. The financial sector, notably Sharia banking through Green Zakat innovations, serves as a vital driver for the net-zero transition. National sustainability success depends on the synergistic triangulation between the state, market, and society in managing systemic risks. Compliance with global standards such as IFRS S2 and OJK regulations forms the core foundation for environmental resilience and long-term welfare in Indonesia.